Antioxidant, Cytotoxic, and Antibacterial Activities of the Selected Tibetan Formulations Used in Gandaki Province, Nepal. (28th July 2021) - Dhakal, Madan; Poudel, Prakash; Jha, Upma; Jaiswal, Suresh; Joshi, Khem Raj
Abstract : Background and Objective . Tibetan medicine is one of the earliest-known traditional medicines. This study aimed to evaluate the antioxidant, cytotoxic, and antibacterial potential of ethanolic extracts of nine common Tibetan formulations. Materials and Methods . An open-ended and semistructured questionnaire was used for an ethnomedicinal survey of the Tibetan formulations practiced in four Tibetan refugee settlements in Gandaki Province, Nepal. Based on the ethnomedicinal survey data, commonly used nine formulations were selected (Aru-18, Basam, Dadue, Dashel, Mutik-25, Raab Ga Yangzin Tea, Serdok-11, Sugmel-10, and Yungwa-4) to test biological activities. Antioxidant activity was evaluated using the 2, 2-diphenyl-1-picryl-hydrazyl (DPPH) radical scavenging method. The cytotoxicity was examined by using the Allium cepa L. root tip meristem model. Similarly, the antibacterial effect was assessed by using well diffusion and broth dilution methods. Results . An ethnomedicinal survey showed a total of 52 Tibetan formulations were generally used by respondents for common diseases such as stomach disorders, diabetes, and migraine. From the antioxidant activity test, Sugmel-10 showed the highest DPPH free-radical-scavenging activity (IC50 1.8 μ g/ml) and Yungwa-4 showed the lowest activity (IC50 5.2 μ g/ml). Also, from the cytotoxic activity, the A. cepa root meristem model exhibited significant dose- and time-dependent growth suppression in Basam, Dadue, Mutik-25, and Serdok-11 as compared with cyclophosphamide standard drug. Similarly, Basam showed a good antibacterial effect having MIC 20 mg/ml and MBC 100 mg/ml against Enterococci faecalis. Conclusion . Research showed that Tibetan people preferred Tibetan formulations for the treatment and mitigation of several diseases. The result of antioxidant, cytotoxic, and antibacterial activities experimentally justified the ethnomedicinal value of nine common formulations (Aru-18, Basam, Dadue, Dashel, Mutik-25, Raab Ga Yangzin Tea, Serdok-11, Sugmel-10, and Yungwa-4). To the best of our knowledge, this study was performed for the first time in Nepal. Results from this preliminary study open the door to the scientific world to perform extensive pharmacological studies for designing and developing new therapeutic agents.